Experiences With Safer Conception Services for HIV-Serodiscordant Couples at a Referral Hospital in Nairobi, Kenya - Kaggiah, Anne; Kimemia, Grace; Moraa, Hellen; Muiruri, Peter; Kinuthia, John; Roxby, Alison C. (Frontiers in Reproductive Health, 2021)
HIV-serodiscordant couples are an important source of new HIV infections in Africa. Uninfected partners may be at high risk of infection when trying to conceive if the infected partner is not virally suppressed. Multiple strategies targeting safer conception exist, but these services are limited. However, when services are available and used, serodiscordant couples feel protected from HIV transmission, and safe to have children if desired. To successfully introduce, integrate, promote and optimize service delivery of safer conception with HIV care it is crucial to understand how HIV-serodiscordant couples perceive and experience these services. Further, viral load monitoring can be critical to safer conception, but there is limited literature on how it informs partners’ decisions about conception. This qualitative study describes the knowledge, perceptions and experiences of both safer conception services and viral load monitoring among 26 HIV-serodiscordant couples seeking safer conception care at a referral hospital in Nairobi, Kenya. In-depth interviews of HIV-serodiscordant couples were conducted from April to July 2017, and transcripts analyzed to identify themes central to couples’ experience of safer conception services and viral load monitoring. Serodiscordant couples reported success in using some of the safer conception methods, and had positive experiences with healthcare providers. However, despite using the services, some were concerned about HIV transmission to the seronegative partner and baby, while others faced challenges when using PrEP and vaginal insemination. Overall, their motivation to have children overcame their concern about HIV transmission, and they welcomed discussions on risk reduction. Moreover, supportive clinic staff were identified as key to facilitating trust in safer conception methods. Furthermore, viral load monitoring was identified as integral to safer conception methods, an emerging theme that requires further evaluation especially where routine viral load monitoring is not performed. In conclusion, healthcare providers offering safer conception services should build trust with couples, and recognize the need for continual couple counseling to encourage adoption of safer conception services.